Detection of Anti- Ovarian Antibodies and Anti-sperm Antibodies in Sera of Sub Fertile Women in Baghdad - Farhan A Risan (Journal of Global Pharma Technology, 2018)
The study was  carried out through  the period  March/2017 to  October/2017,for   estimate the ant ovarian antibodies and anti sperm antibodies in  sera (fifty  nine) sub fertile women  compared with( twenty seven ) healthy women as control  group.  Their mean aged 28 years. The diagnosis of  anti ovarian antibodies concentration   were  a done  by enzyme linkage immunosorbent  assay(ELISA)  A high  significant in cement (p≤ 0.001 ) was observed  in the  sera of sub fertile women( 819 uL) compared  with  control  group( 476uL),while   the anti-sperm antibodies concentration  show high significant in cement (p≤ 0.0l) in the sera of sub fertile women(211 uL) compared with control group(42  UL).Keywords:  Anti-ovarian antibodies, Anti-sperm antibodies, Sub fertile women.